Hygro-mechanical modeling of restrained ring test: COST TU1404 benchmark. (30th December 2019) - Šmilauer, Vít; Havlásek, Petr; Gasch, Tobias; Delaplace, Arnaud; Bouhjiti, David E.-M.; Benboudjema, Farid; Briffaut, Matthieu; Kanavaris, Fragkoulis; Azenha, Miguel
Highlights: Six teams simulated ring shrinkage test using different hygro-mechanical models. Experimental data for desorption isotherm, E modulus, strength evolution, basic creep. Validated mass loss and axial deformation of a prism, hoop strain in the ring. Interface effect between concrete and steel explored. Negligible role of concrete notch. Abstract: The restrained ring test belongs to a traditional method for estimating cracking tendency of a paste, mortar or concrete mix. The test involves hygro-mechanical interactions with intricate interplay of several phenomena, such as autogenous shrinkage, drying shrinkage, basic and drying creep, together with evolution of tensile strength and fracture energy. The benchmark described in this paper relies on extensive experimental data sets obtained through the extended Round Robin Testing programme (RRT+) of COST Action TU1404. Six teams took part with their simulation models. A series of outputs were produced, starting from mass loss of a prism through its axial deformation up to hoop stress/strain evolution in the ring. Four teams quantified also damage due to drying and strain concentrations. All models showed excellent performance on mass loss while strain validation showed higher scatter and influence of several factors. The benchmark demonstrated high capability of used models and emphasized strong role of calibration with regards to available experimental data.